2003
DOI: 10.1017/s0950268803008719
|View full text |Cite
|
Sign up to set email alerts
|

A special risk group for hepatitis E infection: Turkish agricultural workers who use untreated waste water for irrigation

Abstract: Untreated waste water usage in agriculture is an important health-threatening issue which could affect both workers' and the public's health. In this study we researched hepatitis E infection in 46 of 57 farmers who used untreated waste water in agriculture. We compared them with 45 persons of the same socio-economic status and age. Anti-HEV seropositivity was 34.8% in the workers and 4.4% in the control group. We suggest that this type of irrigation is an important potential risk for hepatitis E infection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
32
0
5

Year Published

2007
2007
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(38 citation statements)
references
References 3 publications
1
32
0
5
Order By: Relevance
“…An increased seroprevalence has also been reported in Turkish farmers who used untreated wastewater for agriculture [Ceylan et al, 2003]. These reports support the present study's findings of high HEV RNA positivity rate in the sewage.…”
Section: Discussionsupporting
confidence: 91%
“…An increased seroprevalence has also been reported in Turkish farmers who used untreated wastewater for agriculture [Ceylan et al, 2003]. These reports support the present study's findings of high HEV RNA positivity rate in the sewage.…”
Section: Discussionsupporting
confidence: 91%
“…In a study in which farmers who used unrefined waste water as irrigation water in Diyarbakır and the control group were compared, the HEV seropositivity was found to be 34% in the farmers who used waste water for irrigation and 4.4% in the control group; the difference was markedly different (15). In a study conducted in our country which involved pediatric patients from the province of Konya, the prevalence of anti-HEV was reported to be 5.7% and the HEV seropositivity was found to be markedly increased in conditions where the water source was outside the house compared to the conditions where the water source was inside the house (16).…”
Section: Discussionmentioning
confidence: 99%
“…A separate study reported that 57% of sewerage workers from India were positive for IgG anti-HEV [21]. Turkish farmers who used untreated water for agriculture were highly seropositive for HEV [22]. These studies support the presence of high HEV RNA from sewerage water samples.…”
Section: Discussionmentioning
confidence: 78%